2007
DOI: 10.1016/j.ejphar.2007.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Opioid agonist efficacy predicts the magnitude of tolerance and the regulation of μ-opioid receptors and dynamin-2

Abstract: It has been proposed that opioid agonist efficacy may play a role in tolerance and the regulation of opioid receptor density. To address this issue, the present studies estimated the in vivo efficacy of three opioid agonists and then examined changes in spinal mu-opioid receptor density following chronic treatment in the mouse. In addition, tolerance and regulation of the trafficking protein dynamin-2 were determined. To evaluate efficacy, the method of irreversible receptor alkylation was employed and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 43 publications
(57 reference statements)
7
82
0
Order By: Relevance
“…We allowed a week before testing for postsurgical recovery, and to insure that this single injection of the weak partial agonist nalbuphine would not influence our results with MOR agonists or antagonists. Studies have shown that nalbuphine is a relatively weak partial agonist at MORs (Traynor et al, 2002), and that there is little change in MOR binding even after continuous 7-day exposure to more potent agonists in vivo (Pawar et al, 2007).…”
Section: Surgerymentioning
confidence: 99%
“…We allowed a week before testing for postsurgical recovery, and to insure that this single injection of the weak partial agonist nalbuphine would not influence our results with MOR agonists or antagonists. Studies have shown that nalbuphine is a relatively weak partial agonist at MORs (Traynor et al, 2002), and that there is little change in MOR binding even after continuous 7-day exposure to more potent agonists in vivo (Pawar et al, 2007).…”
Section: Surgerymentioning
confidence: 99%
“…It is widely speculated that differences in short-term MOR regulatory events underlie the profound agonist-selective differences observed in the development of tolerance in vivo (Whistler et al, 1999;Stafford et al, 2001;Walker and Young, 2001;Patel et al, 2002;Grecksch et al, 2006;Pawar et al, 2007). There is no consensus, however, on which elements of MOR regulation-signaling efficacy, desensitization, internalization, or resensitization-are most directly correlated with tolerance (Whistler et al, 1999;Bohn et al, 2000;Williams et al, 2001;Connor et al, 2004;von Zastrow, 2004;Bailey and Connor, 2005;Koch et al, 2005).…”
Section: Enkephalin (Me) [D-alamentioning
confidence: 99%
“…Both opioid agonists and antagonists have been shown to regulate -opioid receptor density (Chakrabarti et al, 1997;Zaki et al, 2000;Rajashekara et al, 2003), and these changes can have an impact on the potency of opioid agonists (e.g., Stafford et al, 2001;Patel et al, 2003). The efficacy of an opioid agonist has been proposed to play an important role in -opioid receptor regulation (Patel et al, 2002;Pawar et al, 2007). For example, chronic treatment with high-efficacy agonists (e.g., etorphine, DAMGO) can induce internalization and down-regulation of -opioid receptors in vitro and in vivo Keith et al, 1998;Whistler and von Zastrow, 1998).…”
mentioning
confidence: 99%
“…For example, chronic treatment with high-efficacy agonists (e.g., etorphine, DAMGO) can induce internalization and down-regulation of -opioid receptors in vitro and in vivo Keith et al, 1998;Whistler and von Zastrow, 1998). Conversely, low-efficacy agonists (e.g., morphine, oxycodone) are less likely to produce either internalization or down-regulation (Keith et al, 1998;Pawar et al, 2007;however, see Haberstock-Debic et al, 2005). Chronic treatment with opioid antagonists (e.g., naltrexone, naloxone) has been shown to up-regulate -, ␦-, and -opioid receptors Lesscher et al, 2003;Patel et al, 2003) and increase the potency of opioid agonists (functional supersensitivity) (Yoburn and Inturrisi, 1988;Yoburn et al, 1989Yoburn et al, , 1995.…”
mentioning
confidence: 99%
See 1 more Smart Citation